2018
DOI: 10.1002/cmdc.201700793
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Target Interaction of Naturally Occurring Muraymycin Nucleoside Antibiotics

Abstract: Muraymycins are a subclass of antimicrobially active uridine-derived natural products. Biological data on several muraymycin analogues have been reported, including some inhibitory in vitro activities toward their target protein, the bacterial membrane enzyme MraY. However, a structure-activity relationship (SAR) study on naturally occurring muraymycins based on such in vitro data has been missing so far. In this work, we report a detailed SAR investigation on representatives of the four muraymycin subgroups A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 40 publications
2
48
0
Order By: Relevance
“…The minimum inhibitory concentration (MIC) displays the relative antibiotic potency of AZM and each derivative against a common strain of bacteria ( Staphylococcus aureus) . The protocol used for the determination of the MIC was as previously described with minor modifications . Staphylococcus aureus subsp aureus Rosenbach (ATCC 6538) were grown in 5 mL of Bacto TM Tryptic Soy Broth medium for 16 hours at 37°C with shaking (250 rpm) when an aliquot was diluted X1000 into 4.5 mL of fresh medium and incubated until OD 600 reaching 0.4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum inhibitory concentration (MIC) displays the relative antibiotic potency of AZM and each derivative against a common strain of bacteria ( Staphylococcus aureus) . The protocol used for the determination of the MIC was as previously described with minor modifications . Staphylococcus aureus subsp aureus Rosenbach (ATCC 6538) were grown in 5 mL of Bacto TM Tryptic Soy Broth medium for 16 hours at 37°C with shaking (250 rpm) when an aliquot was diluted X1000 into 4.5 mL of fresh medium and incubated until OD 600 reaching 0.4.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol used for the determination of the MIC was as previously described with minor modifications. 24…”
Section: Antibiotic Activitymentioning
confidence: 99%
“…Both for potential applications and for more straightforward SAR studies, several simplified muraymycin analogues have been designed [34][35][36][37][38]. By comparison of different natural products and synthetic analogues with long alkyl side chains, it was shown that increased lipophilicity improves antibacterial activities (MIC values), but has only a minor effect on MraY inhibition [17,20,39,40]. This is probably owed to an improved cellular uptake of lipophilically decorated muraymycins.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably owed to an improved cellular uptake of lipophilically decorated muraymycins. Through design of simplified analogues, the terminal urea dipeptide motif [40] as well as the 5 -O-aminoribosyl substituent [21,39] were identified to mediate key interactions in MraY inhibition. However, synthetically obtained 5 -defunctionalized ( 5 -deoxy') muraymycin C4 that was reported by our group [38] was found to still inhibit MraY in the nM range, even though most naturally occurring muramycins are MraY inhibitors with pM activities [39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation